Pemerintah dan Media Sosial Studi Deskriptif Kuantitatif Persepsi Pegawai Humas dan Protokol SETDA Surakarta Terhadap Media Sosial - Nurrohman, M. Farid, Dian Purworini, MM, Nieldya Nofrandilla, MA (2016)
This study aims to determine employess's perceptions of public relations and protocol in SETDA Surakarta on characteristics of social media. Using quantitative descriptive method and form a questionnaire as a data collection instrument. The object of research is all employees of public relations and protocol SETDA Surakarta totaling 19 people. Datas were analyzed using basic statistical analysis with frequency distribution then presented in tabular form. The results showed that the respondent perception of social media has a total score of 1414, a mean of 74.24 and the median number is 72.00 with standard deviations worth of 7.676. This values placing the perception of respondents in positive category. Based on a datas, well known that the participation dimension has the highest average value, indicated that the presence of social media are able to stimulate the respondents behaviour became an active user in generating content and sharing information. The openness dimension has the lowest score, but included in the positive category. Respondents proved, that openness character of social media was demonstrated by the ease in expressing their opinions, exchange information and ideas and ease of giving or receiving comment through the features of the social media.